Effects of different bacterial bioremediator with ammonia removal activity on grouper culture water - Md. Yassin, Farha Fazidah (2013)
Bacterial bioremediators were isolated from microalgae and grouper culture water. Three potential bioremediators were isolated each from microalgae Chlorella vulgaris and grouper culture water. The total ammonia degradation test showed that all strains degraded ammonia at 0.5 ppm. The strain BP-GRP/2 was further tested to grouper juveniles culture. Although, no significant differences can be seen on TAN and SRP, nitrite level was decreased in the presence of the strain. The fish also survived (100% survival) well compared to control (67% survival) in eight days of experiment. The strain was a Gram-negative bacterium by using Gram staining method and molecularly identified as Aeromonas hydrophila by 16S rRNA gene sequencing. These results showed that certain bacterial strain can act as bioremediator and improve the survival of the host.